Management Models of Guidance and Counseling Services to Increase Performance Based on Android Applications - Awalya, Awalya; Khiyarusoleh, Ujang; Oktava, Muhamad Aditya; Gumelar, Fikri Arif; Fajriyani, Dian Safitri Indah (Konseling Edukasi : Journal of Guidance and Counseling, 2023)
Management Models of Guidance and Counseling Services to Increase Performance Based on Android Applications. Guidance and counseling service activities in schools can now be assisted by technological advances, one of which is online-based. The success of the counselor's performance as part of the education system is influenced by many factors such as the ability to master the use of technology and the implementation of its management. This study aims to produce a product in the form of a guidance and counseling teacher management model to improve performance based on android applications. This study uses the Research and Development method, namely a research design that aims to produce or develop a product in the form of models, designs, prototypes, materials, media, tools or strategies, in order to improve the quality of learning by involving partners, namely SMK Negeri 7 Semarang City, Central Java. The population in this study were guidance and counseling teachers or counselors in the city of Semarang with purposive sampling. Data analysis in this study used the Wilcoxon test with an error rate of 5% with the help of SPSS 23.0. The results of this study produce a product in the form of an android application that can provide information related to the performance of guidance and counseling services, so that the administrative process of guidance and counseling teachers becomes more effective and efficient. This application is called SiMakan (Android-Based Counselor Management System) which contains several parts including planning, organizing, controlling, actuating. Management of guidance and counseling services is expected to assist the administrative process so that guidance and counseling teachers have more time to maximize service activities for students.Keywords: Counseling Service, Management Model of Guidance and Counseling.